Naur Klaci Tradition In Belok Sidan Mountainous Village Petang District Badung Regency - Puspawati, Luh Putu (International Journal of Psychosocial Rehabilitation, 2020)
Belok Sidan Village is a mountainous village consisting of many Banjar such as Banjar Sekarmukti, Banjar Peniket, Banjar Sidan, Banjar Belok, Banjar Lawak, Banjar Selantang, Banjar Jempanang, Banjar Bon. Each banjar has different oral traditions in terms of naur klaci (dowry) in a marriage. Each village tradition is unique,Banjar Sekarmukti with Balinese pigs, Banjar Pemiket with Balinese pigs, Banjar Sidan with Balinese pigs, Banjar Bon with Balinese pigs, Banjar Belok with pigs, Banjar Lawak with money, Banjar Selantang with Balinese cows, Banjar Jempanang with Balinese pigs. In each Banjar, the naur klaci (dowry) were carried out at Balai Banjar, Village Temple, a crossroad, or at the banjar hall as a sacred tradition. The bridegroom from the same village have to pay a dowry only once, Bali pigs, female cows, and so on. But if the bridegrooms are from outside the village has to pay double the amount what villagers paid. The data collection was undertaken by observation, interviews, and literature study. The writing technique is descriptive qualitative analytic methods. This study uses a semiotic theory from Ferdinnad De Saussure. The study found that the naur kelaci was carried on from generation to generation. Hence, the people in the village of Belok Sidan needs to keep balinese cows and pigs. Furthermore, the population of balinese cattle and pigs will be maintained. The ritual also includes environmental preservation, religious meaning, and also social meaning.